Deconstructing the map of the paradigm struggle: tracing a nationwide debate on “I do not get it” in Art Magazine (Meishu) - Nan Li; Dawei Lu (Humanities & Social Sciences Communications)
Abstract Understanding the contemporaneity of non-Western art has gained significant attention from scholars across various academic disciplines and different countries. With respect to the notion of “contemporaneity” of contemporary Chinese art, the related theoretical struggles suggest a complex paradigm map that consists of the geographically distinct sociocultural, economic, ideological, political, historical, ethnic and gender characteristics of the PRC. Thus, if discourse is a “gene pool” for interpreting research outcomes, from which scholars can extract a specific range of knowledge, draw on statements and establish their theoretical frameworks, the shaping of discourse and the ensuing theoretical paradigm struggle are more likely to influence one’s scholarly judgements, particularly in his or her exploratory research. This study acknowledges Pierre Bourdieu’s understanding of discourse as an essential tool for exploring the invisible forces within a field, as well as his focus on the reproduction of power within the realms of cultural production and consumption from a cultural sociological viewpoint. On this basis, this study traces a large-scale academic debate sparked by a reader’s letter to Art Magazine (Meishu) when China underwent a series of significant cultural and social transformations in the early 1980s. Through thematic analysis, this article illustrates how the symbolic value and cultural meaning of the “internationalized” art discourse have changed among specific groups of artists and visitors within the Chinese sociocultural context. This article demonstrates that the debate among mainstream critical paradigms, including essentialism, postmodernism-structuralism, and deconstructionism, does not necessarily imply a consequence of a zero-sum game or a struggle for discursive hegemony. While each paradigm has paradoxical issues for understanding the “contemporaneity” of contemporary Chinese art, they may still be able to coexist.